2018
DOI: 10.1186/s12937-018-0422-2
|View full text |Cite
|
Sign up to set email alerts
|

Higher dietary magnesium intake is associated with lower body mass index, waist circumference and serum glucose in Mexican adults

Abstract: BackgroundObesity and diabetes mellitus (DM) are public health concerns in Mexico of top-level priority due to their high prevalence and their growth rate in recent decades. The accumulation of adipose tissue leads to an unbalanced release of pro-oxidant factors, which causes cellular damage and favors the development of comorbidities. Recent evidence suggests that oxidative stress also promotes the accumulation of adipose tissue and the development of insulin resistance. The objective of this study is to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 56 publications
2
35
0
2
Order By: Relevance
“…[27][28][29] Higher physical activity and Mg intake were associated with better glycemic control and lower BMI. 30,31 These published findings aligned with the causal models developed in the present investigation in which physical activity was associated with…”
Section: Discussion and Con Clus I Onsupporting
confidence: 87%
See 1 more Smart Citation
“…[27][28][29] Higher physical activity and Mg intake were associated with better glycemic control and lower BMI. 30,31 These published findings aligned with the causal models developed in the present investigation in which physical activity was associated with…”
Section: Discussion and Con Clus I Onsupporting
confidence: 87%
“…Meta‐analyses of more than 20 investigations showed that increased Mg intake was associated with higher physical activity and lower HbA1c 27‐29 . Higher physical activity and Mg intake were associated with better glycemic control and lower BMI 30,31 . These published findings aligned with the causal models developed in the present investigation in which physical activity was associated with higher Mg intake, lower BMI and decreased HbA1c.…”
Section: Discussionsupporting
confidence: 86%
“…However, our results differed for energy, carbohydrate and PUFA intakes, i.e., we did not identify significant differences across tertiles of C-DII. These findings show that within the Mexican diet, a higher intake of total fat and saturated fat and a lower consumption of fiber along with β-carotene, vitamin C, vitamin E and magnesium (known for having anti-inflammatory and antioxidant properties) [30] during extended periods in childhood could contribute to detrimental health outcomes, including a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 93%
“…Among those observational studies, much research has been undertaken on whether there exists a relationship between magnesium contribution through dietary food and different cardiovascular risk factors, diabetes and cardiovascular diseases [38]. Thus, some studies have reported inverse associations between dietary magnesium intake and body mass index (BMI) or obesity [39,40], blood pressure [40,41], total cholesterol/LDL-cholesterol concentrations [42], and fasting glucose or type-2 diabetes [41,43,44], but the overall consistency for some of these factors is still low. Regarding the incidence of cardiovascular diseases, some studies have reported that high magnesium intake is associated with a lower risk of stroke, heart failure and total cardiovascular events [45,46], but less agreement has been observed for other cardiovascular events [38,47].…”
Section: Introductionmentioning
confidence: 99%